Strategies for the development of the Bajomulyo Coastal Fishing Port, Pati, Central Java - Muhammad Irham Khoirul Jauhari; Agus Suherman; Imam Triarso (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
The fishing port has an important role in supporting activities in the fishery sector which includes serving as a place of preparation, and where to land catches as well as market them. Therefore, this research aims to analyze the level of facilities utilization at CFP Bajomulyo using SOAR and assign the development strategy. The research was carried out in January 2021 at the Coastal fishing port in Bajomulyo Village, Juwana District, Pati Regency. A descriptive method was used to analyze the condition of basic, functional and supporting facilities at CFP Bajomulyo. Data collection was carried out using survey methods and direct observations. The result showed 116% of the pier has been used (overutilized), 26% of the FAP building has been used (non-optimally), 36% of the shipping lane’s depth has been used, meaning the depth is sufficient or in accordance with the required standard, and 49% of its width has been used (non-optimally). Conclusively, the development strategies suggested include making an MoU between the government of Pati Regency and Central Java Province and always considering the availability of FRS facilities, ice factories, clean water, and ship docking around CFP Bajomulyo.Keywords:Development strategyPatiCFP BajomulyoSOAR